Determination of the effect of force rate in ductile polymer / Ahmad Azizi Mohammed and Henry Petrus - Mohammed, Ahmad Azizi; Petrus, Henry (1997)
The purpose of this experiment is to obtain the common properties of actual engineering materials. In the engineering design of structures, components and machines, the 'elastic' properties of the materials used must be accurately known. Elasticity and plasticity are the microscopic properties of large section or parts as opposed to the microscopic properties that are studied in solid-state physics. 'Failure' is the ultimate condition to be avoid in any structural part. The nature of structural failure can be studied experimentally, but only by "destructive testing". A part may fail in tension, compression, torsion, bending, fatigue, etc. and a corresponding number of test isolate or emphasize each kind of failure. Such test are satisfactory if a "sample" of the material can be used, but if the ultimate structure, machine or part is to be checked for defect or for conformity with specifications, some kind of non-destructive test (NDT) must be employed.